2017
DOI: 10.1002/smll.201700920
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-Induced Ge Uniformly Distributed in N-Doped Carbon Nanotubes with Enhanced Li-Storage Performance

Abstract: Germanium (Ge) is a prospective anode material for lithium-ion batteries, as it possesses large theoretical capacity, outstanding lithium-ion diffusivity, and excellent electrical conductivity. Ge suffers from drastic capacity decay and poor rate performance, however, owing to its low electrical conductivity and huge volume expansion during cycling processes. Herein, a novel strategy has been developed to synthesize a Ge@N-doped carbon nanotubes (Ge@N-CNTs) composite with Ge nanoparticles uniformly distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Besides, enhanced electrochemical properties could be achieved by carbon coated Zn 2 GeO 4 microrods . Also, N‐doped carbon nanotubes could be the substrate for capillary‐induced Ge . In addition, Fang et al recently reported that carbon‐coated Bi 2 O 3 nanocomposite is electrochemically active, and its performance can be further improved via a porous carbon buffer layer .…”
Section: Active Anode Materials Incorporated With Porous Carbonaceousmentioning
confidence: 99%
“…Besides, enhanced electrochemical properties could be achieved by carbon coated Zn 2 GeO 4 microrods . Also, N‐doped carbon nanotubes could be the substrate for capillary‐induced Ge . In addition, Fang et al recently reported that carbon‐coated Bi 2 O 3 nanocomposite is electrochemically active, and its performance can be further improved via a porous carbon buffer layer .…”
Section: Active Anode Materials Incorporated With Porous Carbonaceousmentioning
confidence: 99%
“…3b) represent a series of cathodic/anodic peaks below 0.5 V contributed from alloying/dealloying of Ge. 17,27 Besides these peaks, in the first curve a cathode peak at (Fig. S1f).…”
Section: Resultsmentioning
confidence: 93%
“…As electrode and host materials in supercapacitors and Li‐sulfur batteries, respectively, HPCNT/S composites exhibited robust structural stability (Figure g–h). Similar to CNFs, CNTs as versatile substrates are widely utilized in rational design and fabrication of high performance electrode materials in advanced battery systems ,…”
Section: Multiscale Pcns and Their Composites In Advanced Batteriesmentioning
confidence: 99%